2019
DOI: 10.1101/821678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZCWPW1 is recruited to recombination hotspots by PRDM9, and is essential for meiotic double strand break repair

Abstract: During meiosis, homologous chromosomes pair (synapse) and recombine, enabling balanced segregation and generating genetic diversity. In many vertebrates, recombination initiates with double-strand breaks (DSBs) within hotspots where PRDM9 binds, and deposits H3K4me3 and H3K36me3. However, no protein(s) recognising this unique combination of histone marks have yet been identified.We identified Zcwpw1, which possesses H3K4me3 and H3K36me3 recognition domains, as highly co-expressed with Prdm9. Here, we show that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 76 publications
3
13
0
Order By: Relevance
“…Immunofluorescence images in this study revealed that Zcwpw1 functioned in DNA repair and synapsis. Very recently, Zcwpw1 was identified as a histone H3K4me3 reader required for the repair of PR domain zinc finger protein 9-dependent DNA DSBs and synapsis by three independent research groups ( 49 , 50 , 51 , 52 ), which was consistent with our observations. Tesmin and 1700102P08Rik have also recently been identified as essential genes in spermatogenesis ( 53 , 54 ), yet their mechanisms of involvement in meiosis-essential biological events still require further exploration.…”
Section: Discussionsupporting
confidence: 92%
“…Immunofluorescence images in this study revealed that Zcwpw1 functioned in DNA repair and synapsis. Very recently, Zcwpw1 was identified as a histone H3K4me3 reader required for the repair of PR domain zinc finger protein 9-dependent DNA DSBs and synapsis by three independent research groups ( 49 , 50 , 51 , 52 ), which was consistent with our observations. Tesmin and 1700102P08Rik have also recently been identified as essential genes in spermatogenesis ( 53 , 54 ), yet their mechanisms of involvement in meiosis-essential biological events still require further exploration.…”
Section: Discussionsupporting
confidence: 92%
“…Immunofluorescence images in this study divulged that Zcwpw1 played a role of DNA repair and synapsis. Recently, Zcwpw1 was identified as a histone H3K4me3 reader required for synapsis and repair of PRDM9-dependent DSBs by other three research groups [37][38][39][40] , which was consistent with our observations. Whereas, knockout of the other two genes, Tesmin and 1700102P08Rik, were found have no effect on DNA repair and synapsis, indicating they could be involved in presently unknown molecular events inspected by midPachytene checkpoint.…”
Section: Dissucssionsupporting
confidence: 92%
“…In addition to specifying the locations of DSBs, PRDM9 has recently been discovered to play a second role, in the downstream repair of DSBs (Huang et al 2020; Mahgoub et al 2020; Wells et al 2020). In mice and humans, DSBs at which PRDM9 is bound on both homologs are more likely to be efficiently repaired and to result in a crossover; in contrast, DSBs at which PRDM9 is only bound on one of the two homologs are delayed in their repair (Hinch et al 2019; Wells et al 2020). If these “asymmetric” DSBs are overwhelming in number—as is the case in certain hybrid crosses in mice—this delay can lead to asynapsis and infertility (Davies et al 2016; Gregorova et al 2018).…”
Section: Introductionmentioning
confidence: 99%